2020
DOI: 10.24052/bmr/v11nu02/art-01
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance banks and growth of micro, small and medium enterprises in emerging economies: Evidence from Nigeria

Abstract: This study examined the nexus between microfinance banks and the growth of micro, small and medium enterprises in Nigeria. Research design method through a self-administered questionnaire to respondents was adopted for the study. The respondents comprise the microfinance banks’ management and staff and micro, small and medium business entrepreneurs, in Lagos State, the commercial hub of Nigeria. The targeted population of this study was 250 with 223 validly responded. The study tested two hypotheses using logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…According to Aladejebi (2019), the majority of small to medium enterprises experience positive sales growth through participation in micro-credit schemes, which results in increased sales revenue. According to research done by Akinadewo (2020), there is a positive nexus between microfinance products and SME growth. MFI loans have a positive connection with SME sales growth.…”
Section: Firm Sizementioning
confidence: 99%
See 1 more Smart Citation
“…According to Aladejebi (2019), the majority of small to medium enterprises experience positive sales growth through participation in micro-credit schemes, which results in increased sales revenue. According to research done by Akinadewo (2020), there is a positive nexus between microfinance products and SME growth. MFI loans have a positive connection with SME sales growth.…”
Section: Firm Sizementioning
confidence: 99%
“…The positive changes showed that Small to Medium Enterprises are mainly using Microfinance loans for business purposes. According to Akinadewo (2020), microfinance banks and other microfinance institutions have been confirmed to have a positive impact on smallto medium-sized enterprise profits. Variables such as profitability have been examined, and their connection to microfinance loans has been proven.…”
Section: Mfi Loans and Sme Profitabilitymentioning
confidence: 99%
“…Financial reporting quality refers to the extent to which financial information presented by a company in its financial statements accurately and faithfully reflects the economic reality of its underlying transactions and events [19]. High financial reporting quality implies that the financial statements are reliable and transparent, and provide users with a true and fair view of the company's financial position, performance, and cash flows [1]. Financial statements should be free from material errors or omissions, providing users with dependable information for decisionmaking.…”
Section: Financial Reporting Qualitymentioning
confidence: 99%
“…Financial reporting plays a pivotal role in providing relevant information to stakeholders, enabling them to make informed decisions about investments [1]. However, the prevalence of financial fraud and misreporting has raised concerns about the accuracy and reliability of financial statements [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation